Kapasitas Refleksif Pemuda dalam Transisi Menuju Dunia Kerja - Sutopo, Oki Rahadianto; Meiji, Nanda Harda Pratama (JSW: Jurnal Sosiologi Walisongo, 2017)
This article tries to explain the role of reflexive capacity among young people during transition to work. Specifically, four informants in this research are representations of middle class youth from Yogyakarta. This research applies qualitative methods and in-depth interviews as techniques to gather data. This article shows the relevancy of reflexive capacity as a form of embodied cultural capital. Young people whom possess high volume of reflexive capacity will be able to understand the shift of rule of the game in the field and responds quickly and strategically. Furthermore, this reflexive capacity is important as a pre-requirement to anticipate present and future risk. On the other hand, reflexive capacity is only one of entry points among other forms of capital because in reality, young people have to actively negotiate with multilayers structural forces which objectively exist.Â